2020
DOI: 10.1039/c9cc06967d
|View full text |Cite
|
Sign up to set email alerts
|

Cyclam-based antibacterial molecules eradicate Gram-negative superbugs with potent efficacy against human corneal infection

Abstract: Cyclam-based antibacterial molecules (CAMs) that display potent activity against both the planktonic and stationary phase of multidrug-resistant Gram-negative bacteria were rationally designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Additionally, positive charge provided by the cationic amino acid residue di-amino butyric acid and a significant hydrophobicity due to the amino acids phenylalanine and leucine play an essential role in their effectiveness. Cyclam-based derivatives have been designed to mimic this class of antibiotics [ 128 ]. The cyclic molecular backbone was mimicked by the incorporation of cyclam, and the lipophilicity was promoted by conjugating different long-chain fatty acids.…”
Section: Antimicrobial Alternatives Under Investigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, positive charge provided by the cationic amino acid residue di-amino butyric acid and a significant hydrophobicity due to the amino acids phenylalanine and leucine play an essential role in their effectiveness. Cyclam-based derivatives have been designed to mimic this class of antibiotics [ 128 ]. The cyclic molecular backbone was mimicked by the incorporation of cyclam, and the lipophilicity was promoted by conjugating different long-chain fatty acids.…”
Section: Antimicrobial Alternatives Under Investigationmentioning
confidence: 99%
“…Phenylalanine and leucine were also introduced in the structure. The results revealed that longer aliphatic chains led to an increase in the antibacterial activity against A. baumannii , P. aeruginosa , E. coli, and K. pneumoniae [ 128 ]. The most active compound showed a potent activity in the concentration range of 2–8 μg/mL to both wild-type and drug-resistant clinical isolates of those bacteria.…”
Section: Antimicrobial Alternatives Under Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The resultant versatility has enabled the application of cyclam derivatives across a wide range of areas including chemosensing, 5,6 biomimicry, 7,8 molecular switches, 9,10 supramolecular systems, 11,12 catalysis, [13][14][15] and medicine. [16][17][18] Pendant groups including amine, alcohol, thiol, ester, carboxylic acid, amide, carbamate, urea, sulfonamide, nitrile, thioester, pyridyl, triazolyl and phosphonate functionality have been incorporated on side-arms of varying length and complexity, 2,3 to modulate properties such as chelate effects, the selectivity of metal ion-binding, side-chain reactivity, and pendant lability.…”
Section: Introductionmentioning
confidence: 99%
“…3 The resultant versatility has enabled the application of cyclam derivatives across a wide range of areas including chemosensing, 5,6 biomimicry, 7,8 molecular switches, 9, 10 supramolecular systems, 11,12 catalysis, [13][14][15] and medicine. [16][17][18] Pendant groups including amine, alcohol, thiol, ester, carboxylic acid, amide, carbamate, urea, sulfonamide, nitrile, thioester, pyridyl, triazolyl and phosphonate functionality have been incorporated on side-arms of varying length and complexity, 2,3 to modulate properties such as chelate effects, the selectivity of metal ion-binding, side-chain reactivity, and pendant lability.…”
Section: Introductionmentioning
confidence: 99%